PPR pipe with copper resistance and preparation method thereof
By adding activated carbon and copper anti-oxidant 1024, supported by amino/amine modifications, to the inner layer of the PPR tube, the aging problem of PPR pipeline in the presence of copper ions is solved, and the copper corrosion resistance is significantly improved and service life.
Patent Information
- Application Number
- CN202510001851.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-02
AI Technical Summary
PPR pipelines are prone to aging and leakage in the presence of copper ions, resulting in shorter service life and increased maintenance costs.
The activated carbon and anti-copper antioxidant 1024 supported by amino/amine modifications of crosslinked chitosan nano-microspheres were added to the inner layer of the PPR tube to improve the ability to adsorb and complex copper ions through synergistic effects.
It significantly improves the copper corrosion resistance of PPR pipelines, extends service life, and reduces post-maintenance costs, while meeting the sanitary performance requirements for conveying drinking water.
Smart Images

Figure CN119391089A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PPR pipes for building water supply, and in particular to a PPR pipe with copper resistance and a preparation method thereof. Background Art
[0002] PPR pipe is a commonly used water supply pipe material. Due to its good heat resistance, pressure resistance, corrosion resistance and easy processing, it is widely used in construction, chemical industry, food and other fields. PPR pipe is usually connected with pipe fittings with copper inserts by hot melt welding to form water pipelines. Studies have shown that polyolefin materials are extremely sensitive to copper ions. In the presence of copper ions, the degradation and aging of materials such as PE and PP will be accelerated. When there are copper ions in the water, under the combined aging effects of hot water, oxygen and copper ions for a long time, PPR pipes will have "copper damage" problems, resulting in leakage and bursting of pipes during use.
[0003] In order to solve the problem that olefin materials are susceptible to "copper damage", anti-copper agents are mainly added at present. Chinese patent application number 201310413501.8 discloses a polyphosphate anti-copper agent-containing polypropylene composite material and a preparation method thereof, which is processed into a blend by adding polyphosphate anti-copper agent, inorganic filler, antioxidant, ultraviolet absorber and flame retardant into polypropylene; Chinese patent application number 201310411050.4 discloses a polypropylene composite material containing aminocarboxylic acid type anti-copper agent and a preparation method thereof, which is different from Chinese patent application number 201310413501.8 in that the anti-copper agent is an aminocarboxylic acid type anti-copper agent; the polypropylene composite materials prepared by the above two anti-copper agents are suitable for the insulation coating materials of copper core cables, but their adsorption of free copper ions is weak, and their application in PPR pipes is limited.
[0004] How to solve the "copper damage" problem of PPR pipes and improve the copper damage resistance of PPR pipes is an important research direction of polypropylene material modification, which has important scientific significance and practical value. Therefore, a new solution is needed to improve the copper corrosion resistance of PPR pipes to extend their service life and reduce the subsequent maintenance costs. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a PPR pipe with anti-copper performance and a preparation method thereof. The present invention adds activated carbon loaded with amino / amine-modified cross-linked chitosan nano-microspheres and anti-copper antioxidant 1024 to the inner layer of the PPR pipe to synergistically improve the ability to adsorb and complex copper ions and have long-term effectiveness, thereby effectively solving the "copper damage" problem of the PPR pipe, and the formed PPR pipe meets the hygienic performance requirements for transporting drinking water.
[0006] To achieve the above object, the technical solution adopted by the present invention is: In a first aspect, the present invention provides an anti-copper masterbatch, comprising the following components in parts by weight: Modified activated carbon 6-22 parts; random copolymer polypropylene resin 33-76.5 parts; antioxidant and anti-copper agent 1024 5-10 parts; titanium dioxide 5-16 parts; pigment 3-8 parts; compatibilizer 0.5-2 parts; dispersant 0.5-2 parts; lubricant 3-5 parts; coupling agent 0.5-2 parts; The modified activated carbon comprises activated carbon and amino / amine-modified cross-linked chitosan nano-microspheres loaded on the activated carbon; the activated carbon is treated with alkali and acid in advance.
[0007] In the present invention, random copolymer polypropylene resin is used as the anti-copper masterbatch carrier resin, so that the anti-copper additive is evenly distributed therein, and has high compatibility with the PPR resin, which is beneficial to better dispersion of the anti-copper additive and to improve the pressure resistance of the PPR pipe. Activated carbon can adsorb copper ions and simultaneously adsorb cross-linked chitosan nano-microspheres containing amino / amine group modifications, so that the latter are evenly dispersed in the resin and synergistically adsorb copper ions in water. Antioxidant anti-copper agent 1024 has antioxidant and anti-copper properties, but as the antioxidant effect is consumed, the anti-copper effect gradually weakens. When used in combination with activated carbon containing cross-linked chitosan nano-microspheres containing amino / amine group modifications, the anti-copper effect can be significantly improved.
[0008] Therefore, the present invention adds activated carbon loaded with amino / amine-modified cross-linked chitosan nano-microspheres and anti-copper antioxidant 1024 to the inner layer of the PPR pipe. The synergistic effect of the amino / amine-modified cross-linked chitosan nano-microspheres, activated carbon and antioxidant and anti-copper agent 1024 is beneficial to improving the ability to adsorb and complex copper ions and having long-term effectiveness, thereby effectively solving the "copper harm" problem of the PPR pipe, and the formed PPR pipe meets the hygienic performance requirements for transporting drinking water.
[0009] In the present invention, titanium dioxide can improve the whiteness and hiding power of the masterbatch, improve the appearance color and light transmittance; the pigment colors the masterbatch and improves the appearance color. The compatibilizer improves the compatibility of the modified activated carbon, the antioxidant and copper-resistant agent 1024 and the random copolymer polypropylene carrier resin, and improves the stability and processing performance of the mixture. The dispersant can promote the pigment to be evenly dispersed in the resin and no longer agglomerate. The melting point of the dispersant is lower than that of the resin, and the dispersant has good compatibility with the resin and good affinity with the pigment. The lubricant reduces the friction resistance of the mixed material during the processing, thereby improving the processability of the copper-resistant additive, the pigment and the carrier resin. The coupling agent is used to further enhance the combination of the activated carbon, the antioxidant and copper-resistant agent 1024, the pigment and the carrier resin, and improve the dispersibility of the filler.
[0010] In the amino / amine modified cross-linked chitosan nano-microspheres of the present invention, " / " represents an "or" relationship.
[0011] Preferably, the mass ratio of the amino / amine-modified cross-linked chitosan nano-microspheres to the activated carbon in the modified activated carbon is 1:(50-80).
[0012] Preferably, the particle size of the amino / amine-modified cross-linked chitosan nanoparticles is 10-30 nm.
[0013] Preferably, the amino / amine group includes at least one of an aminoethyl group, an aminopropyl group, an aminovinyl group, and an ethylenediamine group.
[0014] Further preferably, the amino / amine-modified cross-linked chitosan nano-microspheres include epichlorohydrin amino-modified cross-linked chitosan nano-microspheres and / or polyethyleneimine-modified cross-linked chitosan nano-microspheres.
[0015] The cross-linked chitosan nano-microspheres modified with epichlorohydrin amine groups have a particle size of 10-25 nm and were purchased from Qingdao University; the cross-linked chitosan nano-microspheres modified with polyethyleneimine have a particle size of 20-30 nm and were purchased from Xi'an Qiyue.
[0016] Preferably, the deacetylation degree of the chitosan is 80%-90%.
[0017] Preferably, the activated carbon includes at least one of coconut shell activated carbon, fruit shell activated carbon, wood activated carbon and coal activated carbon.
[0018] Preferably, the particle size of the activated carbon is 250-400 mesh.
[0019] Preferably, the activated carbon pretreatment method comprises the following steps: The activated carbon is soaked in an alkaline solution for 1-2 hours; then the alkali-washed activated carbon is soaked at 80-85°C for 2-3 hours; then the acid-washed activated carbon is washed with pure water; finally, it is dried at 110-120°C for 10-12 hours to obtain the pretreated activated carbon.
[0020] In the present invention, after the activated carbon is washed with alkali, not only can impurities be removed, but also the pores of the activated carbon can be developed. After acid washing, the pores of the activated carbon can be effectively enlarged, the specific surface area can be increased, and metal ions and other impurities on the surface of the activated carbon can be removed at the same time, and the alkaline groups can be neutralized. In addition, after acid washing, the surface of the activated carbon will have more -COOH, -OH functional groups, which are easier to combine with the cross-linked chitosan microspheres with amino / amine modification, and the activated carbon with more active groups on the surface enhances its compatibility and dispersibility with polyethylene resin. Therefore, by alkali-acid treatment, it is beneficial to improve the ability of activated carbon to load chitosan microspheres, which can make the pores of the activated carbon developed, and the functional groups increased on the surface are easier to combine with the cross-linked chitosan modified with amino / amine.
[0021] Preferably, the acid includes at least one of hydrochloric acid, sulfuric acid and nitric acid.
[0022] Preferably, the method for preparing the modified activated carbon comprises the following steps: S1: adding amino / amine-modified cross-linked chitosan nanoparticles into an organic solvent, stirring evenly, and dissolving to obtain a colloidal solution; S2: Add the pretreated activated carbon into the colloidal solution, ultrasonically vibrate, and soak for 5-10 hours; S3: Filter the soaked activated carbon, and finally dry the filtered activated carbon at 80-90° C. for 2-5 hours to obtain modified activated carbon.
[0023] Preferably, the titanium dioxide includes at least one of rutile titanium dioxide and anatase titanium dioxide, preferably rutile titanium dioxide.
[0024] Preferably, the pigment includes at least one of phthalocyanine green, pigment yellow, brilliant orange and carbon black.
[0025] Preferably, the compatibilizer includes at least one of maleic anhydride grafted polypropylene and acrylic acid grafted polypropylene.
[0026] Preferably, the dispersant includes at least one of fatty acids, fatty amides, and fatty esters.
[0027] Preferably, the lubricant includes at least one of PE wax and Fischer-Tropsch wax.
[0028] Preferably, the coupling agent includes at least one of a titanate coupling agent, a silane coupling agent, and an aluminate coupling agent.
[0029] Preferably, the random copolymer polypropylene resin is an ethylene-propylene binary random copolymer polypropylene with an ethylene content of 4%-9%, a melt index of 7-9 g / 10min, and a density of 0.895-0.905 g / m 3 .
[0030] In a second aspect, the present invention further provides a method for preparing an anti-copper masterbatch, comprising the following steps: (1) The modified activated carbon, the compatibilizer and 1 / 2 of the dispersant are uniformly mixed to obtain a mixture 1; (2) Evenly mix the pigment, 1 / 2 of the dispersant and the lubricant to obtain a mixture 2; (3) uniformly mixing the random copolymer polypropylene resin, the antioxidant and anti-copper agent 1024, titanium dioxide, the coupling agent, the mixture 1 and the mixture 2 to obtain the mixture 3; (4) The mixed material is melt-extruded in a twin-screw machine at a temperature of 150-190°C to obtain an anti-copper masterbatch.
[0031] The present invention adopts a three-step mixing process to pre-mix the dispersed activated carbon and pigment and then mix them with the resin, etc., so as to solve the problem that the activated carbon, the pigment and the resin have poor compatibility and are difficult to disperse.
[0032] In a third aspect, the present invention further provides a PPR pipe with anti-copper performance, comprising a PPR outer layer and an anti-copper functional inner layer, wherein the anti-copper functional inner layer comprises a PPR resin and an anti-copper masterbatch.
[0033] Preferably, the mass ratio of the PPR resin to the anti-copper masterbatch is (90-97): (3-10).
[0034] Preferably, the thickness ratio of the outer layer and the inner layer is: PPR outer layer: anti-copper functional inner layer = 9: (0.8-2.5).
[0035] Preferably, the PPR resin is a random copolymer polypropylene resin.
[0036] Preferably, the PPR outer layer comprises PPR resin and masterbatch.
[0037] In a fourth aspect, the present invention further provides a method for preparing a PPR pipe with copper resistance, comprising the following steps: (1) Mix the PPR resin and the anti-copper masterbatch evenly to obtain the anti-copper functional inner layer raw material; mix the PPR resin and the masterbatch evenly to obtain the PPR outer layer raw material; (2) The anti-copper functional inner layer raw material and the PPR outer layer raw material are fed into the inner and outer layer single screw extruders respectively, and co-extruded through a double-layer mold at an extrusion temperature of 210-240°C.
[0038] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention can remove impurities and metal ions on the surface of activated carbon through pretreatment, generate active functional groups on the surface, and easily disperse into the matrix resin; at the same time, the pores of activated carbon can be developed and the surface area can be increased, and the amino / amine-modified cross-linked chitosan microspheres can more easily combine with the functional groups on the surface of activated carbon.
[0039] (2) The amino / amine modified cross-linked chitosan nanoparticles of the present invention have a small particle size, are prone to agglomeration, and are not easy to be evenly dispersed in the resin. They are first loaded onto the outer surface and internal ablation holes of the treated activated carbon particles. The activated carbon with polar groups on the surface is easier to disperse into the matrix resin, thereby achieving a good dispersion effect of the amino / amine modified cross-linked chitosan nanoparticles in the matrix resin.
[0040] (3) The amino / amine-modified cross-linked chitosan nanoparticles of the present invention are effectively loaded onto activated carbon and form a stable adsorption layer on the surface and in the pores of the activated carbon. This can enhance the adsorption effect of activated carbon on copper ions and improve its adsorption capacity and adsorption rate. At the same time, the amino functional groups of the cross-linked chitosan can also form complexes with copper ions, increasing the selectivity and effect of adsorption.
[0041] (4) The stepwise mixing of the preparation of the anti-copper masterbatch of the present invention can effectively improve the agglomeration of the activated carbon and pigment loaded with amino / amine-modified cross-linked chitosan nano-microspheres in the resin, thereby improving the compatibility with the resin and the dispersibility in the resin matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 1 is a schematic diagram of the structure of the PPR pipe of the present invention, 1 is an inner layer with anti-copper function, and 2 is a PPR outer layer. DETAILED DESCRIPTION
[0043] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the protection scope and implementation methods of the present invention are not limited thereto.
[0044] Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0045] PPR resin: T4401, Dushanzi Petrochemical, density 0.895g / m 3 , tensile yield stress 22.4MPa; Activated carbon: Wooden activated carbon, 325 mesh, Hongzhiyuan; Epichlorohydrin amine-modified cross-linked chitosan nanoparticles: particle size 10-25nm, customized by Qingdao University; Random copolymer polypropylene resin: DY-W725EF, Dushanzi Petrochemical, ethylene content 4.8-5.3%, melt index 7-8g / 10min, density 0.897g / m 3 ; Antioxidant and anti-copper agent 1024: Irganox MD1024, BASF; Titanium dioxide: LR108, Longbai; Pigments: Phthalocyanine Green (Green SG1017) and Pigment Yellow (Yellow 29RP), Guangzhou Xiecai; Compatibilizer: Maleic anhydride grafted polypropylene AT2937, Mitsui Chemicals, Japan; Dispersant: Vinyl bisstearamide EBS-P200, Chaoyang Chemical, Indonesia; Lubricant: zinc stearate, commercially available; Coupling agent: silane coupling agent KH550, commercially available.
[0046] The materials in the following examples and comparative examples all adopt the sources of the above materials.
[0047] Example 1 This embodiment discloses an anti-copper masterbatch, comprising the following components in parts by weight: 13 parts of modified activated carbon; 55 parts of random copolymer polypropylene resin; 10248 parts of antioxidant and anti-copper agent; 11 parts of titanium dioxide; 6 parts of pigment; 1 part of compatibilizer; 1 part of dispersant; 4 parts of lubricant; 1 part of coupling agent.
[0048] The modified activated carbon includes activated carbon and amino / amine-modified cross-linked chitosan nano-microspheres loaded on the activated carbon. The mass ratio of the amino / amine-modified cross-linked chitosan nano-microspheres to the activated carbon is 1:50; the particle size of the amino / amine-modified cross-linked chitosan nano-microspheres is 10 nm.
[0049] The preparation method of modified activated carbon comprises the following steps: S1: Soak the activated carbon in sodium hydroxide solution for 1.5 hours; then soak the activated carbon after alkali washing at 85°C for 2 hours; then wash the activated carbon washed with 5% hydrochloric acid solution with pure water; finally, bake at 120°C for 10 hours to obtain the pretreated activated carbon; S2: adding amino / amine-modified cross-linked chitosan into ethanol solvent, stirring evenly, and dissolving to obtain a colloidal solution; S3: adding the pretreated activated carbon into the colloidal solution, ultrasonically vibrating, and soaking for 8 hours; S4: Filter the soaked activated carbon through a filter to remove excess solution, and finally put the filtered activated carbon into a low-temperature oven for rapid drying at a drying temperature of 85°C for 4 hours to obtain modified activated carbon.
[0050] This embodiment also discloses a method for preparing an anti-copper masterbatch, comprising the following steps: (1) The modified activated carbon, the compatibilizer and 1 / 2 of the dispersant are mixed and stirred in a high-speed mixer for 6 minutes to obtain a mixture 1, so that the activated carbon is pre-mixed with the compatibilizer and the dispersant, and the activated carbon is uniformly coated by the compatibilizer and the dispersant, which can improve the compatibility with the carrier resin; (2) Then, the pigment, 1 / 2 of the dispersant and the lubricant are mixed, and stirred for 6.5 minutes using a high-speed mixer to obtain a second mixture. The high-speed mixing and stirring treatment with the dispersant and the lubricant can effectively disperse the powdered pigment evenly and improve the agglomeration of the powdered pigment; (3) Then, random copolymer polypropylene resin, antioxidant and copper-resistant agent 1024, titanium dioxide, coupling agent, mixture 1 and mixture 2 are mixed, and stirred for 8 minutes using a high-speed mixer to obtain mixture 3; (4) The mixed material is fed into the twin-screw main machine through a feeder, and the extrusion temperature from the feed port to the die is set to 150-180°C. The melted extruded material strips are cooled in a water tank and then pelletized to obtain the anti-copper masterbatch.
[0051] This embodiment also discloses a PPR pipe with anti-copper performance, including a PPR outer layer 2 and an anti-copper functional inner layer 1, the structure of which is as follows: Figure 1 As shown. The thickness ratio of the PPR outer layer and the anti-copper functional inner layer is 9:1, DN20×2.8-S3.2 specification tube.
[0052] The anti-copper functional inner layer includes PPR resin and anti-copper masterbatch, and the mass ratio of PPR resin and anti-copper masterbatch is 94:6. The PPR outer layer includes PPR resin and masterbatch, and the mass ratio of the two is 98:2.
[0053] This embodiment also discloses a method for preparing a PPR pipe with copper resistance, comprising the following steps: (1) Mix the PPR resin and the anti-copper masterbatch evenly to obtain the anti-copper functional inner layer raw material; mix the PPR resin and the masterbatch evenly to obtain the PPR outer layer raw material; (2) The anti-copper functional inner layer raw material and the PPR outer layer raw material are respectively fed into the inner and outer layer single-screw extruders, and co-extruded through a double-layer mold at an extrusion temperature of 210-240°C to obtain a PPR pipe with anti-copper performance.
[0054] Example 2 An anti-copper masterbatch comprises the following components in parts by weight: 6 parts of modified activated carbon; 70.5 parts of random copolymer polypropylene resin; 102410 parts of antioxidant and anti-copper agent; 6 parts of titanium dioxide; 3 parts of pigment; 0.5 parts of compatibilizer; 0.5 parts of dispersant; 3 parts of lubricant; 0.5 parts of coupling agent.
[0055] The modified activated carbon includes activated carbon and amino / amine-modified cross-linked chitosan nano-microspheres loaded on the activated carbon. The mass ratio of the amino / amine-modified cross-linked chitosan nano-microspheres to the activated carbon is 1:80; the particle size of the amino / amine-modified cross-linked chitosan nano-microspheres is 30 nm.
[0056] The preparation method of the modified activated carbon and the preparation method of the anti-copper masterbatch are the same as those in Example 1.
[0057] A PPR pipe with anti-copper performance, comprising a PPR outer layer and an anti-copper functional inner layer, the structure of which is as follows Figure 1As shown. The anti-copper functional inner layer includes PPR resin and anti-copper masterbatch, and the mass ratio of PPR resin and anti-copper masterbatch is 90:10. The PPR outer layer includes PPR resin and masterbatch, and the mass ratio of the two is 98:2.
[0058] The preparation method of a PPR pipe with copper resistance is the same as that in Example 1.
[0059] Example 3 An anti-copper masterbatch comprises the following components in parts by weight: 22 parts of modified activated carbon; 38 parts of random copolymer polypropylene resin; 10245 parts of antioxidant and anti-copper agent; 16 parts of titanium dioxide; 8 parts of pigment; 2 parts of compatibilizer; 2 parts of dispersant; 5 parts of lubricant; 2 parts of coupling agent.
[0060] The preparation method of the modified activated carbon and the preparation method of the anti-copper masterbatch are the same as those in Example 1.
[0061] A PPR pipe with anti-copper performance, comprising a PPR outer layer and an anti-copper functional inner layer, the structure of which is as follows Figure 1 The anti-copper functional inner layer includes PPR resin and anti-copper masterbatch, and the mass ratio of PPR resin and anti-copper masterbatch is 97:3. The PPR outer layer includes PPR resin and masterbatch, and the mass ratio of the two is 98:2.
[0062] The preparation method of a PPR pipe with copper resistance is the same as that in Example 1.
[0063] Example 4 The difference from Example 1 is that when the activated carbon is treated with alkali acid in advance, the activated carbon after alkali washing is soaked in a 5% by mass sulfuric acid solution at 85° C. for 1.5 h, and the rest is the same as Example 1.
[0064] Example 5 The difference from Example 1 is that when the activated carbon is treated with alkali acid in advance, the activated carbon after alkali washing is soaked in a 4% by mass nitric acid solution at 85° C. for 1.5 h, and the rest is the same as Example 1.
[0065] Comparative Example 1 This comparative example provides a PPR pipe, the raw material composition of which is PPR of Dushanzi Petrochemical T4401.
[0066] Comparative Example 2 This comparative example provides a PPR pipe, the raw material composition of which is PPR of Dushanzi Petrochemical T4401, and 0.5 parts of antioxidant and anti-copper agent 1024 are added.
[0067] Comparative Example 3 This comparative example provides a PPR pipe, the raw material composition of which is PPR of Dushanzi Petrochemical T4401, and 0.5 parts of commercially available antioxidant 1010 and 0.5 parts of commercially available antioxidant 168 are added.
[0068] Comparative Example 4 The difference from Example 1 is that the antioxidant and anti-copper agent 1024 is not added to the raw materials of the anti-copper masterbatch, and the rest is the same as Example 1.
[0069] Comparative Example 5 The difference from Example 1 is that no modified activated carbon is added to the raw materials of the anti-copper masterbatch, and the rest is the same as Example 1.
[0070] Comparative Example 6 The difference from Example 1 is that the activated carbon does not carry amino / amine-modified cross-linked chitosan nanoparticles, and the rest is the same as Example 1.
[0071] Comparative Example 7 The difference from Example 1 is that the activated carbon is loaded with cross-linked chitosan nano-microspheres not modified with amino / amine groups, that is, the activated carbon is loaded with cross-linked chitosan nano-microspheres, and the rest is the same as Example 1.
[0072] Comparative Example 8 The difference from Example 1 is that the activated carbon is not pre-treated with alkali or acid, and the rest is the same as Example 1.
[0073] Comparative Example 9 The difference from Example 1 is that the activated carbon is only treated with alkali in advance, and the rest is the same as Example 1.
[0074] Comparative Example 10 The difference from Example 1 is that the activated carbon is only treated with acid in advance, and the rest is the same as Example 1.
[0075] Comparative Example 11 The difference from Example 1 is that the raw materials used in the preparation of the anti-copper masterbatch are simultaneously put into a high-speed mixer and mixed and stirred at one time. The rest is the same as Example 1.
[0076] Performance Testing The performance of the PPR pipes obtained in the above examples and comparative examples were tested respectively, and the specific test items, test methods and results are as follows: (1) Low temperature drop hammer impact test The test method is as follows: ① Sampling: Randomly select 1 pipe (3 meters / piece or 4 meters / piece).
[0077] ② Sample preparation and treatment: After the pipe has cooled completely naturally, cut the pipe for testing within 6 hours after it is offline; cut the pipe into sample tubes about 15 cm long, and ensure that the sample tubes are intact, without obvious deformation and burrs on the end faces; place the sample tubes in a water sink and treat them in a 0℃ refrigerator or 0℃ cooling box for 1 hour.
[0078] ③ Test: The test instrument uses a drop hammer impact tester, and a d25 hammer head is selected for testing. After the state of the sample tube is adjusted, the sample tubes are taken out from the water bath one by one, and the test is completed within 10 seconds. Ten samples of each type of tube are tested; the drop hammer height is set to 1m, the initial weight of the drop hammer is 1.0kg, and the weight is increased by 0.5kg each time, and the results of the cracking of the test sample tube are recorded.
[0079] (2) PPR pipe anti-copper performance test The test method is as follows: Prepare tap water with high copper ion content of 10mg / L, pour the tap water containing copper ions into the PPR test sample tube, seal both ends of the PPR tube, and immerse the PPR tube in a 60℃ insulated water tank. Take samples every fifteen days to test the changes in the oxidation induction time OIT and the hydrostatic pressure resistance (95℃, 22h, 4.3MPa hydrostatic pressure stress) of the PPR tube. Among them, the oxidation induction time is tested according to GB / T 19466.6-2009 standard; the hydrostatic pressure test is tested according to GB / T 6111-2003 standard.
[0080] The test results of low temperature drop hammer performance and copper resistance of the PPR pipes prepared in the above examples and comparative examples are shown in Tables 1-5 below.
[0081] Table 1 Test results of low temperature drop hammer and oxidation induction time of PPR pipe Table 2 Hydrostatic performance test results of PPR pipes Table 3 Hydrostatic performance test results of PPR pipes Table 4 Hydrostatic performance test results of PPR pipes Table 5 Hydrostatic performance test results of PPR pipes As shown in Tables 1-5, the present invention forms an anti-copper functional layer by adding amino / amine-modified cross-linked chitosan nanospheres loaded with activated carbon and anti-copper antioxidant 1024 to the PPR pipe, thereby improving the ability to adsorb and complex copper ions and significantly improving the anti-copper and anti-aging properties of the PPR pipe. The activated carbon can be effectively improved by acid-base treatment and segmented mixing with pigments, etc., to improve the agglomeration phenomenon in the resin, and improve the compatibility with the resin and the dispersibility in the resin matrix.
[0082] In Comparative Examples 1-3, antioxidants 1024, 1010 and 168 were directly added to the PPR pipes, and the initial oxidation induction time was significantly improved, and the anti-oxidation aging performance was enhanced. However, after 60 days, the oxidation induction time decreased significantly. Analysis showed that this may be due to the fact that copper ions accelerated the degradation and aging of PPR, and the pure antioxidant and anti-copper agent 1024 had limited ability to complex copper ions, and antioxidants 1010 and 168 had no anti-copper aging performance. Under the action of long-term heat, oxygen and copper ions, the pressure resistance of the pipe decreased, increasing the risk of pipe burst.
[0083] In Comparative Examples 6-10, when no activated carbon loaded with amino / amine-modified cross-linked chitosan nanospheres was added, activated carbon loaded with non-amino / amine-modified cross-linked chitosan nanospheres was added, and the added activated carbon was not subjected to alkali-acid treatment, the ability of the activated carbon to adsorb and complex copper ions was reduced, the degradation and aging of the PPR was obvious, and the heat and hydraulic resistance were reduced; at the same time, Comparative Examples 8-10 showed that the activated carbon was not treated with alkali-acid, the activated carbon was unevenly dispersed in the PPR substrate, the low-temperature drop hammer performance was reduced, the loading of amino / amine-modified cross-linked chitosan nanospheres was reduced, and the anti-copper and anti-aging properties were also reduced.
[0084] In Comparative Example 11, a one-time mixing and stirring method was adopted, and the activated carbon loaded with amino / amine-modified cross-linked chitosan nanospheres, antioxidant and anti-copper agent 1024, and pigment had poor dispersion and agglomeration. The low-temperature drop hammer performance of the pipe was significantly deteriorated, and the anti-oxidation and aging performance was also significantly reduced.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An anti-copper masterbatch, characterized in that: The composition comprises the following components in parts by weight: Modified activated carbon 6-22 parts; random copolymer polypropylene resin 33-76.5 parts; antioxidant and anti-copper agent 1024 5-10 parts; titanium dioxide 5-16 parts; pigment 3-8 parts; compatibilizer 0.5-2 parts; dispersant 0.5-2 parts; lubricant 3-5 parts; coupling agent 0.5-2 parts; The modified activated carbon comprises activated carbon and amino / amine-modified cross-linked chitosan nano-microspheres loaded on the activated carbon; the activated carbon is treated with alkali and acid in advance.
2. The anti-copper masterbatch according to claim 1, characterized in that: The mass ratio of the amino / amine-modified cross-linked chitosan nano-microspheres to the activated carbon in the modified activated carbon is 1:(50-80).
3. The anti-copper masterbatch according to claim 1, characterized in that: The particle size of the amino / amine-modified cross-linked chitosan nano-microspheres is 10-30 nm.
4. The anti-copper masterbatch according to claim 1, characterized in that: At least one of (a) to (d): (a) the amino group / amine group includes at least one of aminoethyl, aminopropyl, aminovinyl, and ethylenediamine; (b) the deacetylation degree of the chitosan is 80%-90%; (c) the activated carbon comprises at least one of coconut shell activated carbon, fruit shell activated carbon, wood activated carbon and coal activated carbon; (d) The particle size of the activated carbon is 250-400 mesh.
5. The anti-copper masterbatch according to claim 1, characterized in that: The pretreatment method steps of the activated carbon are as follows: The activated carbon is soaked in an alkaline solution for 1-2 hours; then the alkali-washed activated carbon is soaked at 80-85°C for 2-3 hours; then the acid-washed activated carbon is washed with pure water; finally, it is dried at 110-120°C for 10-12 hours to obtain the pretreated activated carbon.
6. The anti-copper masterbatch according to claim 5, characterized in that: The preparation method of the modified activated carbon comprises the following steps: S1: adding amino / amine-modified cross-linked chitosan nanoparticles into an organic solvent, stirring evenly, and dissolving to obtain a colloidal solution; S2: Add the pretreated activated carbon into the colloidal solution, ultrasonically vibrate, and soak for 5-10 hours; S3: Filter the soaked activated carbon, and finally dry the filtered activated carbon at 80-90° C. for 2-5 hours to obtain modified activated carbon.
7. The anti-copper masterbatch according to claim 1, characterized in that: At least one of (a) to (g): (a) the titanium dioxide comprises at least one of rutile titanium dioxide and anatase titanium dioxide; (b) the pigment comprises at least one of phthalocyanine green, pigment yellow, brilliant orange and carbon black; (c) the compatibilizer comprises at least one of maleic anhydride grafted polypropylene and acrylic acid grafted polypropylene; (d) the dispersant comprises at least one of fatty acids, fatty amides, and fatty esters; (e) the lubricant comprises at least one of PE wax and Fischer-Tropsch wax; (f) the coupling agent comprises at least one of a titanate coupling agent, a silane coupling agent, and an aluminate coupling agent; (g) The random copolymer polypropylene resin is ethylene-propylene binary random copolymer polypropylene.
8. The method for preparing the anti-copper masterbatch according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) The modified activated carbon, the compatibilizer and 1 / 2 of the dispersant are uniformly mixed to obtain a mixture 1; (2) Evenly mix the pigment, 1 / 2 of the dispersant and the lubricant to obtain a mixture 2; (3) uniformly mixing the random copolymer polypropylene resin, the antioxidant and anti-copper agent 1024, titanium dioxide, the coupling agent, the mixture 1 and the mixture 2 to obtain the mixture 3; (4) The mixed material is melt-extruded in a twin-screw machine at a temperature of 150-190°C to obtain an anti-copper masterbatch.
9. A PPR pipe with copper resistance, characterized in that: It comprises a PPR outer layer and an anti-copper functional inner layer, wherein the anti-copper functional inner layer comprises a PPR resin and the anti-copper masterbatch according to any one of claims 1 to 7.
10. The method for preparing a PPR pipe with copper resistance according to claim 9, characterized in that: The following steps are involved: (1) Mix the PPR resin and the anti-copper masterbatch evenly to obtain the anti-copper functional inner layer raw material; mix the PPR resin and the masterbatch evenly to obtain the PPR outer layer raw material; (2) The anti-copper functional inner layer raw material and the PPR outer layer raw material are fed into the inner and outer layer single screw extruders respectively, and co-extruded through a double-layer mold at an extrusion temperature of 210-240°C.
Citation Information
Patent Citations
An amino carboxylic acid type copper inhibitor polypropylene composite material and its preparation method
CN103554651B
A polypropylene composite containing a polyphosphate copper inhibitor and a preparation method thereof
CN103554653B
High-strength nano-antibacterial PPR pipe and preparation method thereof
CN108194713A
Preparation of anti-ultraviolet ageing and antimicrobial wood-plastic composite material filled and modified with chitosan modified silver nanoparticles
CN108948769A
Black master batch for water supply pipes and preparation method thereof
CN110511476A
Cited By
A copper-resistant additive-resistant PPR multi-layer pipe grafted by micro-crosslinking and a preparation method thereof
CN122688348A